Economic Policy Challenges of Digitisation - Philipp Steinberg; Gero Roser (Wirtschaftsdienst, 2020)
Abstract Digitisation is bringing far-reaching changes for businesses, employees and consumers. It impacts almost all areas of economic activity. The associated changes in the economy and society pose new challenges for economic policy: It must adapt the regulatory framework to enable innovations in new technologies and fields of application, promote Germany’s competitiveness in a digitised world and ensure competition in digital markets. Through experimental clauses, better digital infrastructure and targeted support for companies, it can ensure that innovations can be implemented and brought to market faster. Small and medium sized enterprises benefit particularly from this. Methods of ‘strategic foresight’ can also help to anticipate the future challenges of digitisation at an early stage and find economic policy answers.